STATUS DAN KEDUDUKAN SAKSI PEREMPUAN DALAM HUKUM ISLAM DAN KUHPerdata - Fanani, Zainal; Ansori, Ahmad Insya’ (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. The issue of gender equality that arises essentially lies in human rights (al-kulliyyât al-Khaimah), by placing more equality before the law as the core of equality of opportunity, spreading in the aspect of women's testimony before the law. For this reason, it is important to underline that the main problem of testimony is inseparable from gender. Aim. This research focuses on women's testimony to Islamic law and the Civil Code. Methods. Using comparative techniques with descriptive analysis, the following research results were obtained: the status and position of women as witnesses in religious courts from the point of view of Islamic law, the status of the testimony of one man is the same as that of two women. Results. The point of the difference is not to doubt the ability of women, it's just because in the business world that is done during the day until night men should do the signing and testimony of all kinds of business. Suppose there is a woman who is a witness. In that case, she must have an additional woman who serves to strengthen the testimony they do, because it could be that at any time one of the two is unable to attend to give testimony or has forgotten the object he witnessed in the past. The equal value of male and female testimony in the Law of Civil Procedure in Religious Courts is because the witness is positioned as one of the evidence, the task of witnesses in civil procedural law is to prove the existence or absence of something legal action. In short, if the witness is positioned as a pillar, it must follow as specified in the Qur'an.